The effect of telephone health coaching and remote exercise monitoring for peripheral artery disease (TeGeCoach) on health care cost and utilization: results of a randomized controlled trial - Dirk Heider; Farhad Rezvani; Herbert Matschinger; Jörg Dirmaier; Martin Härter; Lutz Herbarth; Patrick Steinisch; Hannes Böbinger; Franziska Schuhmann; Gundula Krack; Thomas Korth; Lara Thomsen; et al. (The European Journal of Health Economics, 2023)
Background: Peripheral artery disease (PAD) is the third most prevalent atherosclerotic cardiovascular disease. In 2016, costs per patient associated with PAD exceeded even the health-economic burden of coronary heart disease. Although affecting over 200 million people worldwide, a clear consensus on the most beneficial components to be included in home-based exercise programs for patients with peripheral artery disease is lacking. The aim of the study was to examine the health care use and costs caused by the 12-month patient-centered 'Telephone Health Coaching and Remote Exercise Monitoring for Peripheral Artery Disease' (TeGeCoach) program in a randomized controlled trial. Methods: This is a two-arm, parallel-group, open-label, pragmatic, randomized, controlled clinical trial (TeGeCoach) at three German statutory health insurance funds with follow-up assessments after 12 and 24-months. Study outcomes were medication use (daily defined doses), days in hospital, sick pay days and health care costs, from the health insurers' perspective. Claims data from the participating health insurers were used for analyses. The main analytic approach was an intention-to-treat (ITT) analysis. Other approaches (modified ITT, per protocol, and as treated) were executed additionally as sensitivity analysis. Random-effects regression models were calculated to determine difference-in-difference (DD) estimators for the first- and the second year of follow-up. Additionally, existing differences at baseline between both groups were treated with entropy balancing to check for the stability of the calculated estimators. Results: One thousand six hundred eighty-five patients (Intervention group (IG)0.167em=0.167em806; Control group (CG)0.167em=0.167em879) were finally included in ITT analyses. The analyses showed non-significant effects of the intervention on savings (first year: -~352 exteuro; second year: -~215 exteuro). Sensitivity analyses confirmed primary results and showed even larger savings. Conclusion: Based on health insurance claims data, a significant reduction due to the home-based TeGeCoach program could not be found for health care use and costs in patients with PAD. Nevertheless, in all sensitivity analysis a tendency became apparent for a non-significant cost reducing effect. Trial registration: NCT03496948 (www.clinicaltrials.gov), initial release on 23 March 2018
Keywords: I; 610; Peripheral artery disease; Home-based exercise program; Randomised controlled trial; Intention-to-treat; Health care use and costs